Rulings dying person in Islamic jurisprudence (Journal of the College of Basic Education, 2022)
This paper deals with: Rulings dying person in Islamic jurisprudence, and the reason for choosing this topic Because people desperately need to know his rulings.The introductory section deals with: Definition of a dying person, and its signs, and cases, and what does to him, and ruling on his repentance.The first section deals with: The sayings of the jurists in the ruling on the actions of the dying person in financial transactions in buying, selling and the giveaway.The second section deals with: The sayings of the jurists in how to pray the dying person, and how to pay zakat for the dying person.While The Third section deals with: The sayings of the jurists in the ruling on the actions of the dying pe